Social Cohesion in the Interaction Patterns of the Salafi Community in Rensing Raya Village - Ajeng Azizah (Tabéq: Journal of Local Wisdom, Belief, and Peace, 2025)
This study analyses the social interaction patterns of exclusive Salafi groups in building social cohesion in Rensing Raya Village, East Lombok Regency. Salafi groups prioritise exclusive interactions in social life, such as mutual assistance, humanitarian aid, and economic activities, without mixing their religious values in these activities. The exclusive normative attitude of Salafi groups makes them unwilling to compromise with other religious practices, thus forming clear boundaries between them and the local community. Nevertheless, Salafi groups adapt to social activities that do not directly conflict with their beliefs or worship, such as participating in village development. This study reveals that, although their interaction patterns tend to be closed in terms of religious values, Salafi groups remain active in the social and economic life of the community, maintaining a separation between their religious teachings and social life. Therefore, Salafi groups contribute to strengthening social cohesion through their participation in more general social activities, which in turn support more harmonious social relations in Rensing Raya Village.